Physical properties of ZnSe-MgSe, ZnSe-CdS solid solutions and possibilities of their application in IR engineering - Zagoruiko, Yu.A.; Fedorenko, O.A.; Kovalenko, N.O.; Rom, M.A.; Mateychenko, P.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The vertical Bridgman method is used to obtain crystals of Zn₁₋x Mgx Se and ZnSe-CdS solid solutions (with 0.03 Ј x Ј 0.55 and Cd concentrations varying from 0.3 to 35 at.%, respectively). The composition of the samples is determined by means of electron-probe microanalysis. The methods of optical microscopy and X-ray analysis are used to investigate the structure of the crystals and to determine their lattice parameters. Investigated are the micro-hardness and microbrittleness of the grown ZnMgSe crystals, as well as their polarizational, optical, photoelectric and dielectric properties depending on Mg concentration. The obtained crystals are found to possess anisotropy of physical properties. The largest anisotropy of their mechanical, polarizational and optical properties is observed in the crystals containing 5-6 at.% of Mg. The samples with such a concentration of Mg are applicable as a base for making thermostable multifunctional IR optical elements which can operate within a wide spectral region.